Can strategic integration of cultivated pasture legumes into temperate agricultural systems provide stability to honey bee populations and associated industries? - Joanne J. M. Wisdom; Daniel R. Kidd; Megan H. Ryan; Liz Barbour; Alistair Hockey; Gregory R. Cawthray; Kevin J. Foster (Plants, People, Planet)
Societal Impact Statement Humans and honey bees have a long history of interaction to yield valued products and services. However, honey bees are under pressure from changes in vegetation, agricultural practices and climate change. We investigate if pasture legumes can be harnessed to support honey bees. We use a diverse set of species that originated from the Mediterranean and western Europe but are now developed as commercial cultivars for the southern Australian livestock industries. We find that pasture legumes show great promise as a means to support honey bees and suggest that further targeted research is warranted. Summary Globally, humans and honey bees (Apis mellifera) have a long history of interaction and this is now under pressure. In temperate southern Australia, exotic honey bees rely on an unstable native floral resource base, yet a diverse set of exotic pasture legume species are sown as staple rotational or permanent crops. We investigated if these pasture legumes could be strategically used to support honey bee populations for the apiary and horticulture industries in this region. A literature review on temperate pasture legumes and honey bees was undertaken and integrated with data from an Australian industry case study. Comparisons were made to the widely‐grown red clover (Trifolium pratense) and white clover (T. repens). We found that many southern Australian pasture legumes could provide significant floral resources as well as enhanced temporal and spatial stability for honey bees due to phenological variability and broad adaptation. Honey bees will likely recognise and be attracted to their flowers and other characteristics are comparable, or potentially superior, to red and white clover, such as floret number per inflorescence, floret length, nectar volume and sucrose‐dominance and pollen protein. The floral resource diversity from pasture legume mixes could aid honey bee health and support pollinator services for adjacent crops. We conclude that the exotic pasture legumes of temperate Australia show promise for development as a sown floral resource for honey bees. Globally, further investigation is merited to maximise benefits from the integration of a diverse range of pasture legumes into agricultural landscapes.